Comparative Study of the Role of LAZISMU and LAZISNU in Economic Empowerment of Muslim Communities in Kudus - Marsya Rizqia; Tuti Nadhifah; Yunus Mustaqim; Daniel Ferdian (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
The socioeconomic landscape of Kudus Regency presents a significant challenge that necessitates the active role of Islamic philanthropic institutions in allocating zakat, infaq, and alms through productive schemes. In this context, LAZIS Muhammadiyah (LAZISMU) and LAZIS Nahdlatul Ulama (LAZISNU) emerge as the two primary forces, each employing distinct approaches to community empowerment. The ideological divergence between Muhammadiyah, leaning toward a modernist-administrative framework and Nahdlatul Ulama deeply rooted in traditional cultural bases—creates a unique dynamic in their economic strategies. This study aims to conduct a systematic comparative analysis of how these institutions design, implement, and ensure the sustainability of their programs using a qualitative comparative approach. Through field observations, in-depth interviews, and documentation involving institutional boards and beneficiaries, the findings reveal that LAZISMU operates under a highly structured management model. This approach prioritizes bureaucratic efficiency and top-down planning, ranging from capital provision to entrepreneurship training. While LAZISMU excels in targeting accuracy and procedural transparency, it faces challenges in field mentoring, which tends to be inconsistent, impacting the long-term resilience of businesses. In contrast, LAZISNU prioritizes social networks and local cultural capital. By leveraging grassroots activists, LAZISNU fosters a mentoring system that is fluid and intensive. Its kinship-based communication and organic monitoring boost beneficiary confidence and business sustainability. Although its formal administration is less extensive than LAZISMU’s, this socio-cultural approach yields more significant results in long-term independence. This study concludes that effective empowerment requires integrating professional management with sustained social assistance. Success is measured not merely by aid volume, but by the depth of interaction and guidance provided.